Analysis of the Potential and Development Strategy of the Al-Qur’an Al-Akbar as a Religious Tourism Object in the City of Palembang, South Sumatra Province - Lubis, Sri Wulandari; Helmi, Sulaiman (Journal of Social Work and Science Education, 2024)
Indonesian tourism has become a very popular industry, due to its economic impact and benefits. During the COVID-19 Pandemic, tourism was one of the sectors that was severely affected by the economy of most Indonesians. Based on BPS data (2021), there is a significant decrease in the number of tourists in domestic tourists and foreign tourists. The research objective is to determine and analyze the potential and development strategy of Al-Akbar Al-Qur’an as a religious tourist attraction in Palembang City, South Sumatra Province using SWOT analysis. The method used in the preparation of this thesis is the Qualitative Descriptive research method. In this study, the authors used descriptive qualitative methodology. Researchers who conduct qualitative descriptive research must be skilled at explaining, describing, and exploring data based on in-depth interviews with respondents to understand what they say, feel, and do. The result of the research is that the external factors of Al-Akbar Al-Qur’an Tourism are more dominant than the internal factors. The highest value of SWOT owned by Al-Akbar Al-Qur’an Tourism is located in strength with a value of 2.35. Al-Akbar Al-Qur’an Tourism of Palembang City has various potentials and can be developed further if there is good coordination between agencies, managers, and local community support.